A look at the Chinese art market in the second decade of the 21st century (Economic and Political Thought, 2020)
The extremely dynamic development of the Chinese art market, ina broad sense, in recent decades, reflects the growing role of the Chineseeconomy in the world and the growing wealth of Chinese society. In the years2008–2011, this market recorded a growth of 500 proc. unprecedented in anyother region of the world. In 2018, China’s share in the global art market at19 proc. confirmed a strong position of this country as one of the top threeart markets in the world. At the same time, the Chinese auction marketwas second in the world. The People’s Republic of China owes its positionas a world leader above all to the significant economic reforms of recentyears, the effective implementation of the open door policy, and its enormouscultural potential. Chinese culture is a priceless treasure of all mankind,preserved in facilities subject to economic trading. There are few countriesthat can compete in terms of the wealth of artistic activity with China, one ofthe biggest states that are a source of cultural property in the world and oneof the largest art markets. The purpose of the article is to present the mostimportant issues of the Chinese art market in the last two decades.
Keywords: antiques market in China, Chinese culture, Chinese art, auction market in China, art market in China, Chinese Auction Houses, Chinese collectors, Chinese economic reform